Application and discussion of the borehole radial deformation method in deep borehole geostress measurement - Han, Zengqiang; Li, Minghong; Wang, Chao; Wang, Jinchao; Huang, Xiaohua (Frontiers in Earth Science, 2023)
Geostress is an important parameter in rock-related fields, such as civil engineering, mining engineering, and energy engineering. There are kinds of methods for geostress measurement; however, many methods still have some limitations, especially when facing deep vertical boreholes. In this paper, we studied the characteristics of borehole radial deformation under the action of geostress. First, the rule of borehole radial deformation under the action of a two-dimensional geostress was studied, and the shape of the borehole radial changes to an ellipse under the action of geostress was proved. We derived the relationship between the magnitude of principal stresses and the parameters of the borehole ellipse, revealing the rule that the principal axis direction of the borehole ellipse is the direction of principal stress, which is the theoretical basis for the geostress calculation method based on borehole radial deformation measurement. Furthermore, we developed an apparatus that can simultaneously measure the changes in borehole diameters in multi-directions. The apparatus was designed with a multi-contact equidistant arrangement, micro-optical imaging measurement, electronic compass azimuth measurement, etc. It can adapt to the complex testing environment of deep boreholes and realize real-time monitoring of the borehole deformation process. Indoor tests were carried out to verify the working performance of the apparatus. The results showed that the measuring accuracy of the apparatus can reach 6.987 μm, meeting the requirement of geostress measurement. Also, the results are well consistent with the loading force and direction of the testing machine. A field test was carried out in a deep borehole, and the borehole radial deformation data were obtained in the process of stress relief. The feasibility of the instrument and method was verified by comparison with the hydraulic fracturing method. This paper provides a new idea and method for geostress measurement, especially in deep vertical boreholes.